The complete chloroplast genome of Notholition macrophyllum. Issue 2 (3rd July 2018) - Li, Juan; Liu, Haiying; Xie, Dengfeng; Zhou, Songdong; He, Xingjin
Abstract: Notholirion macrophyllum (D. Don) Boiss. (Liliaceae) is a floriferous species naturally distributed in Asia. The complete chloroplast genome sequence of N. macrophyllum was generated by de novo assembly using whole genome next generation sequencing data. The complete chloroplast genome of N. macrophyllum was 152143 bp in total sequence length and divided into four distinct regions: small single copy region (17913 bp), large single copy region (82222 bp) and a pair of inverted repeat regions (26004 bp). The genome annotation displayed a total of 135 genes, including 82 protein-coding genes, 38 tRNA genes, and 8 rRNA genes. Phylogenetic analysis with 7 Liliaceae species revealed that N. macrophyllum was the basal species of tribe Lilieae and was close to Cardiocrinum giganteum .